Lehel Lészai: “Discipleship in the Synoptics”, Presa Universitară Clujeană – Evangelische Verlagsanstalt Leipzig, 2017, ISBN 978-606-37-0276-1 - András László RÁD (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Most of the readers of this journal are used to finding positive reviews in this section written with the purpose of recommending a worthy piece of academic literature to our peers. With the intention of breaking this pattern, allow me to provide the possible readers with a set of warnings with regard to whom I do not recommend this book to. So, if you do not find yourself in any of the predicaments below, do consider picking up a copy of the book as it will not disappoint you.